2004
DOI: 10.1016/j.jacc.2004.08.016
|View full text |Cite
|
Sign up to set email alerts
|

Left ventricular dyssynchrony predicts response and prognosis after cardiac resynchronization therapy

Abstract: Patients with LV dyssynchrony >/=65 ms respond to CRT and have an excellent prognosis after CRT.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

16
790
6
25

Year Published

2006
2006
2018
2018

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 966 publications
(837 citation statements)
references
References 25 publications
16
790
6
25
Order By: Relevance
“…A Bland-Altman analysis was conducted to analyze the agreement between the two velocity measurement techniques (24). Dyssynchrony was assessed as the absolute difference between time to peak systolic velocity in the septal and lateral walls (13,(25)(26)(27). The repeatability of the MR and TDI data was assessed by comparing the peak velocity (both systolic and diastolic) and the time to peak velocity between repeated scans using a Bland-Altman analysis (24).…”
Section: Discussionmentioning
confidence: 99%
“…A Bland-Altman analysis was conducted to analyze the agreement between the two velocity measurement techniques (24). Dyssynchrony was assessed as the absolute difference between time to peak systolic velocity in the septal and lateral walls (13,(25)(26)(27). The repeatability of the MR and TDI data was assessed by comparing the peak velocity (both systolic and diastolic) and the time to peak velocity between repeated scans using a Bland-Altman analysis (24).…”
Section: Discussionmentioning
confidence: 99%
“…A systolic dyssynchrony index (SDI), calculated from tissue Doppler imaging (TDI), proved capable of retrospectively predicting enhanced clinical response in single-center work [83]. These benefits were also observed in a multicenter retrospective analysis where the use of baseline TDI imaging predicted not only functional and echocardiographic improvement but also identified patients who yielded prognostic benefit from CRT [84]. Speckle-tracking radial strain analysis superseded TDI, as it was less dependent on the angle of incidence of the ultrasound beam and also appeared able to predict echocardiographic response in retrospective analysis [85].…”
Section: Dyssynchrony Assessment and Identification Of The Site Of Lamentioning
confidence: 99%
“…CTDI is most commonly used and measures time from QRS onset to peak systolic velocity (TPSV). Bax and colleagues defined dyssynchrony as the maximum difference in TPSV between the four basal (anterior, inferior, septal, lateral) segments 70 and TPSV difference of 65 ms had a sensitivity and specificity of 80% for predicting reduction in death and HF hospitalisation. Yu, et al developed a 12‐segment model involving six basal and mid segments from the three apical views and deriving the standard deviation (SD) between the 12 measurements, thereby creating a dyssynchrony index 71 .…”
Section: Newer Parameters and Applicationmentioning
confidence: 99%
“…Current guidelines 103 recommend CRT for patients on optimal medical therapy with EF ≤ 35%, in NYHA class III or IV with QRS ≥ 120 ms although a subgroup of patients with QRS < 120 ms can benefit from CRT 104 . Single centre studies of CRT response in HF found that improvement was more likely in patients with echocardiographic dyssynchrony at baseline 70 , 105 , 106 . However, two multicenter studies, the PROSPECT 107 and ReThinQ trials 108 , used echocardiographic criteria for patient selection and found only modest correlation between echocardiographic indices and CRT benefit.…”
Section: Role Of Echocardiography In Therapeutic Interventionmentioning
confidence: 99%